Título Padrão - Pinheiro Fagundes, Isabelle; Gonçalves de Macedo Reinaldo, Maria Augusta (Revista de Letras, 2024)
This article aims to analyze the results of an activity focused on teaching Portuguese, with an emphasis on the organization of the academic summary genre, developed with deaf undergraduate students of the Libras course. We adopted as theoretical assumptions Portuguese as a second language for deaf students from a bilingual perspective, sociodiscursive interactionism (SDI), with the notion of a didactic model of genre, and sociorhetoric, with the notion of rhetorical organization. The data analyzed are part of module 3 of a didactic sequence, linked to an ongoing doctoral research. The results indicate that the activity developed provided students with an understanding of rhetorical organization as a relevant dimension that favors the recognition of the essential organizational elements of this genre. The study demonstrates how adapted activities can contribute to the development of linguistic skills and deaf undergraduate students.